The Emperor's New Clothes: Prospective Observational Evaluation of the Association between the Day 2 Vancomycin Exposure and Failure Rates among Adult Hospitalized Patients with MRSA Bloodstream Infections (PROVIDE). (4th October 2017) - Lodise, Thomas P; Rosenkranz, Susan L; Finnemeyer, Matthew; Huvane, Jacqueline; Pereira, Alenda; Sims, Matthew; Zervos, Marcus J; Creech, C Buddy; Patel, Pratish C; Keefer, Michael; Riska, Paul; Silveira, Fernanda P; et al.
Abstract: Background: Current guidelines recommend vancomycin (VAN) dosing to achieve AUC/MIC ratio ≥400 for patients (pts) with serious MRSA bloodstream infections (BSI), but supporting data were largely derived in single center retrospective studies. A recent study using a Bayesian approach to estimate the VAN AUC found that patients with MRSA BSI who had an AUCDAY2 /MICBMD ≥ 650 or an AUCDAY2 /MICETEST ≥ 320 had lower incidences of failure ( Clin Infect Dis 59:666, 2014). This study prospectively evaluated if these VAN AUCDAY2 /MIC targets were associated with lower incidences of failure (PROVIDE, Award number UM1AI104681, Antibacterial Resistance Leadership Group). Methods: Prospective, multi-center ( n = 14), observational study (2014–2106) of hospitalized adults with confirmed MRSA BSI treated with VAN ≥ 72h. Exclusion: (1) neutropenia; (2) cystic fibrosis; (3) renal replacement therapy; (4) APACHE-II score > 25; (5) previous MRSA BSI within 60 days. VAN exposures were estimated using maximum a posteriori probability procedure in ADAPT 5. MICBMD and MICETEST were performed at a central laboratory. Outcomes: failure (30-day mortality or MRSA BSI ≥ 7 days); acute kidney injury (AKI), ≥1.5 × increase in serum creatinine (Scr ) among patients with a baseline SCR < 2.0mg/dl. The study was powered at 80% to detect a 17.5% difference in failure between AUCDAY2 /MIC groups. Results: Among the 265 evaluable patients, mean (SD) age was 61 (17) and APACHE-II was 12 (6). Endocarditis was definite/possible in 29%. The MIC50/90 by BMD and ETEST were 1/1 and 1.5/1.5mg/l, respectively. Failure occurred in 18%; 26% had AKI. Mean (SD) VAN duration was 18 (14) days. Mean (SD) AUCDAY2 was 586.9 (235.5) and 44% and 73% of patients achieved an AUCDAY2 /MICBMD ≥ 650 and AUCDAY2 /MICETEST ≥ 320. In the multivariate analyses (Figure 1), failure was not significantly different between AUCDAY2 /MIC groups. In contrast, AKI was significantly more common in patients with an AUCDAY2 / MICETEST > = 320. Conclusion: Achievement of higher VAN AUCDAY2 /MIC exposures for patients with MRSA BSIs were not associated with better outcomes and were found to result in increased AKI. Clinicians should assess the benefits vs. risks of using VAN regimens that confer high AUCDAY2 /MIC exposures for patients with MRSA BSIs. Disclosures: T. P. Lodise Jr., allergan: Consultant, Grant Investigator, Scientific Advisor and Speaker's Bureau, Consulting fee and Speaker honorarium; medicines company: Consultant, Grant Investigator, Scientific Advisor and Speaker's Bureau, Consulting fee, Research support and Speaker honorarium; melinta: Consultant, Consulting fee; motif: Consultant and Scientific Advisor, Consulting fee; paratek: Consultant and Scientific Advisor, Consulting fee; nabriva: Consultant, Consulting fee; M. J. Zervos, Merck, Inc.: Investigator, Research grant; M. Scheetz, Bayer: Scientific Advisor, Consulting fee; V. Fowler Jr., Pfizer, Novartis, Galderma, Novadigm, Durata, Debiopharm, Genentech, Achaogen, Affinium, Medicines Co., Cerexa, Tetraphase, Trius, MedImmune, Bayer, Theravance, Cubist, Basilea, Affinergy, Janssen, xBiotech, Contrafect: Consultant, Consulting fee; NIH, Basilea, MedImmune, Cerexa/Forest/Actavis/Allergan, Pfizer, Advanced Liquid Logics, Theravance, Novartis, Cubist/Merck; Medical Biosurfaces; Locus; Affinergy; Contrafect; Karius: Grant Investigator, Research grant; Green Cross, Cubist, Cerexa, Durata, Theravance; Debiopharm: Consultant, Consulting fee; UpToDate: author on several chapters, Royalties